THE EPISTEMOLOGICAL ROOTS OF STRUCTURAL REALISM: MODELS AND REPRESENTATION IN INTERNATIONAL RELATIONS THEORY - Peruana de Derecho Internacional, Sociedad (2020)
The text explores some basic ideas about the epistemology behind the theory ofStructural Realism, or Neorealism, by Kenneth Waltz. First, theproblem of descriptive interpretation of theories, particularly in the disciplineof International Relations, as well as certain critical conceptions that arise fromthis logic. Second, the formal structure of the theoretical programs is analyzedin general, with an emphasis on the theoretical structure of Structural Realism. The notion ofthe duality of international political phenomena is described as an elementcentral to the core of empirical laws and principles of theory, defining its purposeand establishing its scope and limitations. Finally, the last section explores thepredictive potential of international relations theories, elaborating acritical approach to these issues from the theory itself. Finally, theconclusions consider the contribution of Waltz's general theory onthe way of thinking theories and their importance for the discipline of RelationsInternationals.